Internalisasi Konsep Ta’dîb Al-Attas dalam Pengembangan Karakter Peserta Didik - M. Arfan Mu’ammar (Universitas Darussalam Gontor, 2013)
The ‘character building’ topic starts as the top topics in discussion latterly. Various training holds sporadically for the executives, teachers, and employer’s company in outbound form or workshop. Those activities are good definitely, but it’s not enough to build a character. We have to combine our efforts systematically and integrated, so the character building as we want can be effective, learnable and known by the others. That’s all because the intellectualities and cognitive capability cannot guarantee for someone to be able to erase his mentality of corruption, collusion and nepotism, etc. In the other side, awkward’s morality can override the student’s intellectualities. Al-Attas as a Muslim scholar, offers a concept of Ta’dib that has been offered and nominated in the first time at the First Islamic Conference at Mecca in 1977. Al-Attas has a notion that everyone who learned is good man and the term ‘good’ here is a behavior that includes of someone’s spiritual life and material, who try to implants kindliness that he accepted it. The good man is a human being who has characters and polite. The internalization concept of Ta’dib inside of Character building is a requirement than we need, especially this times that we have to face some thoughtfulness phenomena’s degradation of moral. This Ta’dib concept leads someone to be able to put something in its place. So, we can create some condition which the structuralist’s fungsional called as well regulated society. If this society does not reflects the well regulate society, then this society still uncultured.